2020
DOI: 10.1016/j.jue.2019.103189
|View full text |Cite
|
Sign up to set email alerts
|

Using purchase restrictions to cool housing markets: A within-market analysis

Abstract: In response to worsening housing affordability resulting from rapid housing price appreciation, governments in some high housing price areas have introduced taxes or restrictions to reduce investment by non-residents in residential real estate. We study the effectiveness of these efforts using the restrictions imposed by local Chinese governments in November 2010 on apartment (condominium units) purchases. Our contribution comes from using data that exploits within city variation in restriction implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Reduce the phenomenon of excessive real estate speculation. This result is determined by user demand rather than the subsequent supply of land market and developers [8].…”
Section: Related Researchmentioning
confidence: 98%
“…Reduce the phenomenon of excessive real estate speculation. This result is determined by user demand rather than the subsequent supply of land market and developers [8].…”
Section: Related Researchmentioning
confidence: 98%
“…Thus, we conducted extra robustness checks by adding the dummy variables for several other policies into Equation (1). The policies we took into account include the resource-exhausted city support policy in 2008, 2009 and 2012 [31], the low-carbon city pilot project in 2010, 2012 and 2017 [32,33], the smart-city pilot project in 2013 and 2015 [34], the clean-winter-heating plan in Northern China in 2017 [35], and the real-estate-purchase restriction policy in different years [36]. After adding the dummy variables of these policies separately or simultaneously into Equation (1), the estimated impact of the SDPRC policy is still significantly negative and very close to our baseline estimate.…”
Section: Robustness Checksmentioning
confidence: 99%
“…Researchers discovered that the directives, including loan‐to‐value policies and down payment ratios, impose liquidity constraints to households and force them to adjust their credit levels, thereby curbing the rise of housing prices (Armstrong et al., 2019; Laufer & Tzur‐llan, 2021; Acharya et al., 2022). The second is purchase quantity limitations that limit the number of properties an individual could purchase (Somerville et al., 2020). Studies indicated that the limitations would cause resources misallocation among consumers (Glaeser & Luttmer, 2003; Lu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The limits policies are varied across cities, for example, targeting investors differences. These limitations prevented buyers, depending on their residency status (Hukou), from purchasing either a second or third property (Somerville et al, 2020). In this regard, our work is mostly related to Sun et al (2017), Jia et al (2018), andLi et al (2020).…”
mentioning
confidence: 99%